(3GdeaGgje(B-(3GdeHGOF(B-(3GdJLGQH (B-(3JWHjbGJ GdMhceI aj GdeUGQas - (3WGQb YHO GdYGd(B, (3MeGOs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI ddfTQ hGdJhRjY(B,s, 2005)
(3MhceI GdTQcGJ(B( (3GdeaGgje, GdNUGFU, GdeHGOF(B-(3GdQcGFR(B) - (3JWHjbGJ MhceI GdTQcGJ aj GdeUGQa(B.s
(3GdeQGLY U(B803.s
Keywords: (3GdTQcGJ(B- (3JfXje h EOGQIs; (3GdeUGQas; (3MhceI GdTQcGJs